Behavioural Credit Cycles - Domenico Delli Gatti; Gabriele Iannotta (Center for Economic Studies and ifo Institute (CESifo), 2022)
We explore the intertwined dynamics of asset prices and the macroeconomy in a Behavioural model of Credit Cycles (BCC) characterized by a credit friction à la Kiyotaki and Moore and heterogeneous expectations cum heuristic switching à la Brock and Hommes. This behavioural approach allows to better understand and replicate the effects of shocks. In the absence of actual defaults, following a positive productivity shock, our behavioural model (BCC Mark I) generates hump-shaped impulse-response functions that are more realistic than those generated by the same shock in a corresponding model with rational expectations (RCC). When the behavioural model allows also for defaults (BCC Mark II), a productivity shock triggers ample and persistent fluctuations (if the intensity of choice of the lender is sufficiently high), a feature that is absent in BCC Mark I (and of course in RCC).
Keywords: E32; E44; D84; 330; credit market; collateral constraints; heterogeneous expectations; bankruptcy; boom bust cycles